2005
DOI: 10.1111/j.1742-4658.2005.04753.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic properties of wild‐type and active site mutants of chitinase A fromVibrio carchariae, as revealed by HPLC‐MS

Abstract: Chitin is a homopolymer of b(1,4)-linked N-acetyl-dglucosamine (GlcNAc) residues and a major structural component of bacteria, fungi, and insects. In the ocean, chitin is produced in vast quantities by marine invertebrates, fungi, and algae [1]. This highly insoluble compound is utilized rapidly, as the sole source of carbon and nitrogen, by marine bacteria such as Vibrio spp. [2,3]. Two types of enzymes are required for the hydrolysis of chitin. The first, chitinases, are the major enzymes, which degrade the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…This enzyme degraded pNP-GlcNAc about 10-fold more efficiently than GlcNAc 2 . As already observed elsewhere [18], GlcNAc 6 is the best substrate and GlcNAc 3 is the poorest substrate. For long chain substrate, colloidal chitin is the best substrate among the long-chain chitin substrates (Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…This enzyme degraded pNP-GlcNAc about 10-fold more efficiently than GlcNAc 2 . As already observed elsewhere [18], GlcNAc 6 is the best substrate and GlcNAc 3 is the poorest substrate. For long chain substrate, colloidal chitin is the best substrate among the long-chain chitin substrates (Fig.…”
Section: Resultssupporting
confidence: 57%
“…We previously reported that a marine bacterium V. harveyi mainly secreted chitinase A (VhChiA), which is a member of family-18 chitinases, to degrade chitin-containing materials from marine biosphere for its energy source [7]. Further cloning and highly expressing recombinant VhChiA in an E. coli system allowed its enzymatic properties in chitin degradation to be investigated in detail [9,11,18]. Recently, crystal structures of VhChiA were solved in the absence or the presence of chitin oligomers [10].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mutation of the middle Asp in the diagnostic DxDxE motif, which interacts with the catalytic Glu during the catalytic cycle, yielded strong TG mutants (50). Correlation between a lower K m and increased TG was observed for the ␤-mannanase Man5A from the blue mussel Mytilus edulis (19), endo-␤-N-acetylglucosaminidase from Mucor hiemalis (39), and chitinase A from Vibrio carchariae (33).…”
Section: Discussionmentioning
confidence: 94%
“…Methods that employ HPLC have also been described for the separation and quantifi cation of chito-oligosaccharides (Krokeide et al 2007 ) . Combination of HPLC and electrospray mass spectroscopy allows the simultaneous separation of a and b anomers, and monitoring of chitooligosaccharide products down to picomoles (Suginta et al 2005 ) . Mass spectroscopy and nuclear magnetic resonance (NMR) were utilized to determine the size of chito-oligosaccharides produced by the activity of chitinases or chemical depolymerisation of chitin (Howard et al 2003 ) .…”
Section: Chromatographic Techniques Facilitate Analysis Of Chitooligomentioning
confidence: 99%